2023
DOI: 10.37201/req/085.2022
|View full text |Cite
|
Sign up to set email alerts
|

Emergency detection of HIV infection in patients consulting for conditions potentially related to occult infection: Initial results of the “Urgències VIHgila” program

Abstract: Objective. To estimate the prevalence of unknown HIV infection in patients who consulted in hospital emergency services (ED) for conditions defined in the SEMES-GESIDA Consensus Document (DC), evaluate the efficiency of its im-plementation and investigate the efficiency of HIV serology determination in other conditions. Methods. Results were reviewed in 10 Catalan EDs for 12 months (July-21-June-22) after implementing CD recommendations: request HIV serology in case of suspected sexually transmitted infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…However, even for the current rates of testing, it seems that the targeted strategy designed by SEMES is cost-efficient. Indeed, a preliminary analysis had already demonstrated that positivity was higher than 0.1% for all situations with the exception of HZ [22], and 95% confidence intervals were always greater than 0.1% for all the conditions in the present study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, even for the current rates of testing, it seems that the targeted strategy designed by SEMES is cost-efficient. Indeed, a preliminary analysis had already demonstrated that positivity was higher than 0.1% for all situations with the exception of HZ [22], and 95% confidence intervals were always greater than 0.1% for all the conditions in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…The ‘dejatuhuella’ program is carried out in Catalonia under the project ‘VIHgila’. They have recently published their results showing that there are 4 clinical situations in which the request for an HIV test could be efficient: lymphopenia, fever with polyarthralgia-polyarthritis, behaviour alteration-confusion-encephalopathy and fever without a clear focus [22]. Based on these results, SEMES must consider including other conditions in the updating of its recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…En el caso del programa "Urgències VIHgila", un punto clave en su diseño fue considerar que los profesionales de enfermería pueden jugar un papel destacado en esta detección, por su permanente presencia en los SUH a lo largo de todo el proceso asistencial, por su proximidad al paciente y por el propio rol de enfermería enfocado a una detección precoz de los problemas de salud y una buena prevención. Diferentes autores han destacado este potencial impacto del equipo de enfermería en la detección precoz de pacientes con infección oculta por el VIH en los SUH y la revisión de la literatura respalda la implementación de estrategias de detección del VIH en urgencias impulsadas por enfermería [24][25][26][27][28] . Por ello, el programa "Urgències VIHgila" cuenta desde su inicio con un referente de enfermería en cada SUH en el que se implementa.…”
Section: Introductionunclassified